PENGARUH BUDAYA KERJA, LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS LINGKUNGAN HIDUP KABUPATEN SIDRAP - NURLIAH NURLIAH; Ahmad Firman; Haeranah Alwany (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
This study aims to analyze the partial and simultaneous effect of work culture, work environment and leadership on the performance of the State Civil Apparatus at the Sidrap Regency Environmental Service Office. This research is a quantitative research with survey method with correlational analysis technique to determine the effect of the relationship between the dependent variable and the independent variable. Data collection methods used are questionnaires and document studies. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results of the study show that 1) Partially indicate that the work culture variable has a dominant effect on employee performance, this indicates that the higher the work culture, the higher the performance of the state civil apparatus at the Sidrap Regency Environmental Service. 2) Partially shows that the work environment variable has an effect on employee performance, this shows that the better the work environment, the better the performance of the state civil apparatus at the Sidrap Regency Environmental Service. 3) Partially shows that the leadership variable has an effect on employee performance, this shows that the better the applied leadership will further improve the performance of the state civil apparatus at the Sidrap Regency Environmental Service. 4) Simultaneously shows that the variables of Work Culture, Work Environment and Leadership affect the Performance of the State Civil Apparatus, which means that the increase in Work Culture, Work Environment and Leadership will affect the increase in the Performance of the State Civil Apparatus of the Environmental Service of Sidrap Regency by 88.9%.